There is only one solution in the given equation -y2 − [-5y − y(-7y − 9)] − [-y (15y + 4)] = 0. In solving this problem, apply first PEMDAS (parenthesis, exponents,multiplication, division, addition, subtraction). Then equation will transform into -y2+5y-7y2-9y+15y2+4y=0. Combine terms with same power and achieve 7y2=0. Divide both sides with 7 and perform square root of zero. Since the root is zero, we have one solution of the given equation which is y=0.
40x+8x^2=0 can be solved for x (there are two solutions):
Divide all 3 terms by the greatest common multiple (which is 8x):
40x+8x^2=0
------------- -----
8x 8x
5 + x = 0 produces the root x = - 5.
Setting 8x = 0 and solving for x produces the root x = 0.
Be certain to check these results. substitute x = -5 into 40x+8x^2=0. Is the resulting equation true or false? Next, subs. x=-5 into 40x+8x^2=0. Is the resulting equation true or false?
Answer:
![a_1=-10](https://tex.z-dn.net/?f=a_1%3D-10)
![d=3](https://tex.z-dn.net/?f=d%3D3)
Step-by-step explanation:
we know that
In an <u><em>Arithmetic Sequence</em></u> the difference between one term and the next is a constant, and this constant is called the common difference (d)
In this problem we have the ordered pairs
Let
![a_1=-10\\a_2=-7\\a_3=-4\\a_4=-1\\a_5=2\\a_6=5](https://tex.z-dn.net/?f=a_1%3D-10%5C%5Ca_2%3D-7%5C%5Ca_3%3D-4%5C%5Ca_4%3D-1%5C%5Ca_5%3D2%5C%5Ca_6%3D5)
Find the difference between one term and the next
The difference between one term and the next is a constant
This constant is the common difference
so
The sequence graphed is an Arithmetic Sequence
therefore
The first term is
The common difference is equal to
That would be A...they have to have a constant ratio
Answer:
75.40 cm²
Step-by-step explanation:
SA = 2πrh + 2πr²
SA = 2π(2)(4) + 2π(2)²
SA = 50.27 + 25.13
SA = 75.40 cm²